Genetic associations and shared environmental effects on the skin microbiome of Korean twins. (December 2015) - Si, Jiyeon; Lee, Sunghee; Park, Jin; Sung, Joohon; Ko, GwangPyo
Abstract Background The skin is the outermost layer of the human body and one of the key sites for host-microbe interactions. Both environmental and host genetic factors influence microbial communities in distinct anatomical niches, but little is known about their interplay in shaping the skin microbiome. Here, we investigate the heritable components of the skin microbiome and their association with host genetic factors. Results Based on our analysis of the microbiota from 45 individuals including monozygotic and dizygotic twins aged 26–55 years and their mothers, we found that skin microbial diversity was significantly influenced by age and skin pigmentation. Heritability analysis revealed genetic and shared environmental impacts on the skin microbiome. Furthermore, we observed a strong association between the abundance ofCorynebacterium jeikeium and single nucleotide polymorphisms (SNPs) in the host FLG gene related to epidermal barrier function. Conclusion This study reveals an intimate association of the human skin microbiome and host genes, and increases our understanding of the role of human genetic factors in establishing a microbial ecosystem on the body surface.